En mi alcoba agrandada de soledad y miedo: figuraciones de lo violento en la poética de Delmira Agustini - Fernández dos Santos, Mirta (2020)
Criticism coincides, almost unanimously, in pointing out the violent and iconoclastic character of Delmira Agustini's poetic discourse within Hispanic literary modernism. Therefore, after the publication of El libro blanco (1907) ‒ the poems in which Agustini more clearly imitates the modernist aesthetic mania ‒ the princesses, fairies and magicians who populated his verses began to be increasingly replaced by relentless, melancholic and sin- ister figures: statues, snakes, vampires, spiders, owls or bloody swans are gradually becoming frequent images of his poetic imagery. In this way, the author appropriates the classic modern- ist symbols, gives them a new meaning and moves them into gloomy spaces that surprise and disconcert the reader, accustomed to the peaceful and idyllic Rubén Darío ́s environments. Thus, to the violence exerted on the word, there is the unease produced by the scenarios in which the poetic subject frames his compositions: Agustini claims the aesthetics of ugliness and all his poetry, from the publication of Cantos de la mañana (1910), is impregnated with a dark background, in which perverse beasts that cause both fascination and rejection appear. The objective of this article is, then, to analyse these violent poetic environments, relating them to the author's discourse and her exceptional status as a poet-woman in a patriarchal cultural and literary environment.